Global hotspots and prospects of perimenopausal depression: A bibliometric analysis via CiteSpace - Gao, Mingzhou; Zhang, Hao; Gao, Zhan; Sun, Ya; Wang, Jieqiong; Wei, Fengqin; Gao, Dongmei (Frontiers in Psychiatry, 2022)
Background Perimenopausal depression (PMD) is characterized by affective symptoms as well as menopause-specific somatic complaints and has attracted increasing attention over the past few decades. Using a bibliometric tool, this study aims to evaluate the origin, current hotspots, and research trends on PMD. Methods Articles with research on PMD were retrieved from Web of Science Core Collection (WoSCC). We used the bibliometric method to analyze publication years, journals, countries, institutions, authors, research hotspots, and trends. We plotted the reference co-citation network and used keywords to analyze the research hotspots and trends. Results A total of 209 publications related to PMD were identified from WoSCC on May 8, 2022. The number of publications concerning PMD every year shows an upward trend. Further analysis indicated that 209 articles were contributed by 45 countries, 288 institutions, and 501 authors. The United States contributed the most significant number of publications, followed by China. Harvard University is the core institution of PMD research, and Cohen’s work has had an important impact on another research. The occurrence and pathological mechanisms of depression during the menopausal transition from the knowledge base of PMD. All of them belong to the category of gynecology and psychosis, which reflects the focus of the research topics. Major depression, postmenopausal women, symptoms like hot flashes, and prevalence and risk factors are research hotspots in the PMD field. The frontiers in PMD field that will impact future research are anxiety, meta-analysis, association, and Beck Depression Inventory-II (BDI-II). Conclusion These findings provide us with the core countries, institutions, and authors in PMD research and point out the direction of attention in this field. The current research focuses on depression, postmenopausal women, hot flashes, and other symptoms, as well as the prevalence and risk factors. The frontiers will be anxiety, meta-analysis, related factors, and depression assessment in future research.